2020
DOI: 10.1038/s41467-020-18013-7
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase DOT1L coordinates AR and MYC stability in prostate cancer

Abstract: The histone methyltransferase DOT1L methylates lysine 79 (K79) on histone H3 and is involved in Mixed Lineage Leukemia (MLL) fusion leukemogenesis; however, its role in prostate cancer (PCa) is undefined. Here we show that DOT1L is overexpressed in PCa and is associated with poor outcome. Genetic and chemical inhibition of DOT1L selectively impaired the viability of androgen receptor (AR)-positive PCa cells and organoids, including castration-resistant and enzalutamide-resistant cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 67 publications
1
52
0
Order By: Relevance
“…Our results also revealed that DOT1L supports MYC and BACH2 activity, which B cells depend on to effectively differentiate into pro‐proliferative GC B cells and maintain that state (Calado et al , 2012). Recent studies have shown that inhibition of DOT1L also leads to reduced Myc expression in multiple myeloma (Ishiguro et al , 2019), in MYC‐driven B‐cell lymphoma (Deshpande et al , 2018), and in androgen‐dependent prostate cancers (Vatapalli et al , 2020) indicating that the connection between DOT1L and MYC has broad implications in B‐cell physiology as well as other cell types. Furthermore, in neuroblastoma H3K79me2 methylation has been shown to be a strict prerequisite for MYC‐induced transcriptional activation, indicating a mutual interaction between DOT1L and MYC (Wong et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also revealed that DOT1L supports MYC and BACH2 activity, which B cells depend on to effectively differentiate into pro‐proliferative GC B cells and maintain that state (Calado et al , 2012). Recent studies have shown that inhibition of DOT1L also leads to reduced Myc expression in multiple myeloma (Ishiguro et al , 2019), in MYC‐driven B‐cell lymphoma (Deshpande et al , 2018), and in androgen‐dependent prostate cancers (Vatapalli et al , 2020) indicating that the connection between DOT1L and MYC has broad implications in B‐cell physiology as well as other cell types. Furthermore, in neuroblastoma H3K79me2 methylation has been shown to be a strict prerequisite for MYC‐induced transcriptional activation, indicating a mutual interaction between DOT1L and MYC (Wong et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Dot1l was overexpressed in prostate cancer and associated with poor outcome. Chemical or genetic inhibition of Dot1l impaired the viability of androgen receptor-positive prostate cancer cells [ 18 ]. Other studies found that Dot1l epigenetically promoted the transcription of c-Myc via H3K79me2, while silence or inhibition of Dot1l induced cell cycle arrest in colorectal cancer cells, suggesting that Dot1l inhibitor might be a potential drug for the treatment of colorectal cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that in the same publication, the authors did not observe changes in the global levels of AR, emphasizing the subtle roles of SIAH2 in the control of a specific pool of ARs. In a recent work, Vatapalli et al [138] have shown that upregulation of MYCregulated E3 ubiquitin ligases HECTD4 and MYCBP2 promotes AR and MYC degradation that leads to repression of MYC in a negative feed forward manner and regulation of the tumorigenicity of AR-positive prostate cancer cells. Among the most prominent E3 ligases that influence prostate cancer is SKP2, an F-box protein, and a crucial component of the SCF type of E3 ubiquitin ligase complexes.…”
Section: Ubiquitinationmentioning
confidence: 99%
“…prolongs the half-life of the E2F1 protein by inhibiting its ubiquitination (MDM2 displaces SCFSKP2); influences cell proliferation [168] MYCBP2 Atypical E3 ubiquitin-protein ligase, which mediates ubiquitination of threonine and serine, instead of lysine residues AR, MYC [138] Tumorigenicity of AR-positive PCa cells [138] MYLIP E3 ubiquitin-protein ligase whose activity depends on E2 enzymes of the UBE2D family AR [172] AR activity [172] PIRH2 Ring finger protein with ubiquitin ligase activity Epsilon-COP [173]; HDAC1 [174] Regulation of the secretion of PSA [173]; AR signaling [174] pVHL Substrate recognition subunit of the VHL-Elongin B/C E3 ligase complex that targets the HIF-1/2 for proteasomal degradation under normoxia conditions AR (enhanced AR de-ubiquitination instead of inducing AR ubiquitination) [175]; HIF-1α [176] Suppression of AR activity [175]; HIF-1 hypoxic response [176] RNF2 Also known as RING1b or RING2; catalytic subunit of PRC1 TXNIP [177]; CCL2 [178] Cell cycle arrest and apoptosis [177]; metastasis in mice inoculated intracardially with PC-3M cells [178]…”
Section: Mdm2mentioning
confidence: 99%
See 1 more Smart Citation